2001
DOI: 10.1111/j.1728-4457.2001.00687.x
|View full text |Cite
|
Sign up to set email alerts
|

Women's Autonomy in India and Pakistan: The Influence of Religion and Region

Abstract: This article compares the lives of women and explores dimensions of their autonomy in different regions of South Asia-Punjab in Pakistan, and Uttar Pradesh in north India and Tamil Nadu in south India. It explores the contextual factors underlying observed differences and assesses the extent to which these differences could be attributed to religion, nationality, or north-south cultural distinctions. Findings suggest that while women's autonomy-in terms of decision-making, mobility, freedom from threatening re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
413
3
9

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 582 publications
(438 citation statements)
references
References 11 publications
13
413
3
9
Order By: Relevance
“…While we do not claim that the specifics of the Jatti socio-cultural setting will necessarily apply to other parts of Pakistan, we do argue that the generic inadequacies of the 'autonomy paradigm' discussed above are likely to be widely felt for the following reasons. One, the foundational principles underlying gender ideologies and values, kinship systems and concepts of personhood tend to be common over large regions (Jejeebhoy and Sathar, 2001;Dyson and Moore, 1983). Second, gender systems are not isolated structures; they are embedded in political, social and economic contexts (Morgan & Niralua, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…While we do not claim that the specifics of the Jatti socio-cultural setting will necessarily apply to other parts of Pakistan, we do argue that the generic inadequacies of the 'autonomy paradigm' discussed above are likely to be widely felt for the following reasons. One, the foundational principles underlying gender ideologies and values, kinship systems and concepts of personhood tend to be common over large regions (Jejeebhoy and Sathar, 2001;Dyson and Moore, 1983). Second, gender systems are not isolated structures; they are embedded in political, social and economic contexts (Morgan & Niralua, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Jejeebhoy and Sathar noted that traditional forms of authority (such as age) can have a strong effect on women's autonomy in communities with wide gender disparities. 28 An ethnographic study in a working class community in Istanbul, Turkey, questioned the whole idea that education leads to women being empowered and wanting fewer births. 26 Although a study in Pakistan found four ways that education affects fertility (it leads to later marriage, to women marrying men with higher income, to women entering the formal employment sector and to unspecified changes in women's values and interests), it found that domestic autonomy failed to predict fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about antimale bias in the Khasi society (Gurdon, 1981;Pakyntein, 1999), which can be considered as comparable to antifemale bias as in other parts of South Asia including India (Jejeebhoy & Sathar, 2001;Fikree & Pasha, 2004). Among the War Khasis, both sons and daughters inherit the parental property.…”
Section: Role Of Cultural Diversitymentioning
confidence: 99%
“…Nutritional and health discriminations against girls in India may vary from one region to another depending upon a number of cultural factors relating to beliefs, ideas and behaviours that are socially transmitted from one generation Excess male chronic energy deficiencyto another in a specific population or culture area (Jejeebhoy & Sathar, 2001). Subject to further studies, such cultural factors may in turn act as constraints of the so-called universal factors (socio-economic factors) of social and economic change, such as employment, educational and income levels.…”
Section: Role Of Cultural Diversitymentioning
confidence: 99%
See 1 more Smart Citation